2016
DOI: 10.1242/dev.129379
|View full text |Cite
|
Sign up to set email alerts
|

Bmp signaling mediates endoderm pouch morphogenesis by regulating Fgf signaling in zebrafish

Abstract: The endodermal pouches are a series of reiterated structures that segment the pharyngeal arches and help pattern the vertebrate face. Multiple pathways regulate the complex process of endodermal development, including the Bone morphogenetic protein (Bmp) pathway. However, the role of Bmp signaling in pouch morphogenesis is poorly understood. Using genetic and chemical inhibitor approaches, we show that pouch morphogenesis requires Bmp signaling from 10-18 h post-fertilization, immediately following gastrulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 66 publications
5
50
1
Order By: Relevance
“…During pouch segmentation, foxa1 is expressed not only in the medial pharyngeal endoderm but also in the first pouch [34]. Consistent with previous reports [40], the expression of foxa1 was not notably changed in the medial pharyngeal endoderm, but obviously decreased in the first pouch at 26 hpf in embryos treated with 10 μM Dorsomorphin (Fig 4A). Meanwhile, blocking BMP signaling using 10 μM Dorsomorphin also led to decreased expression of nkx2 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…During pouch segmentation, foxa1 is expressed not only in the medial pharyngeal endoderm but also in the first pouch [34]. Consistent with previous reports [40], the expression of foxa1 was not notably changed in the medial pharyngeal endoderm, but obviously decreased in the first pouch at 26 hpf in embryos treated with 10 μM Dorsomorphin (Fig 4A). Meanwhile, blocking BMP signaling using 10 μM Dorsomorphin also led to decreased expression of nkx2 .…”
Section: Resultssupporting
confidence: 90%
“…BMP signaling plays important roles in the induction and anteroposterior patterning of the endoderm during gastrulation [38,39]. However, past work has shown that blocking BMP activity at the early somite stages has no effect on early endoderm genesis [40]. To this end, DMH1-treated Tg(sox17 : GFP) transgenic embryos stably expressed GFP fluorescence in unaltered expression domains at 6- and 10-somite stages when compared with control embryos, suggesting that the pan-endoderm was properly developed (S6 Fig).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fstl1 has a domain similar to follistatin. In addition, its orthologue in zebrafish, zfstl 1/2, functions analogously to nog1 and chd to antagonize BMP activity during zebrafish development [37-39]. Previous reports show that Fstl1 can bind to BMP4 with a K d similar to that of follistatin binding to activin [27, 32, 40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study indicated that endodermal BMP signaling promotes FGF signaling to control pharyngeal pouch development during early somitogenesis (Lovely et al, 2016), suggesting these signals may be expressed at an appropriate developmental time to function downstream of Wnt signaling in patterning PM progenitor cells. However, our analysis of BMP and FGF ligands within zebrafish embryos after Wnt manipulation only revealed patterning defects that are consistent with early axis specification defects without effects on the pharyngeal pouches (Supplementary Material – Figure S6 and Figure S7).…”
Section: Discussionmentioning
confidence: 99%